2006
DOI: 10.1136/hrt.2005.086058
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of multivessel disease on cause-specific mortality after ST elevation myocardial infarction treated with reperfusion therapy

Abstract: Objectives: To investigate the long-term impact of multivessel coronary artery disease (MVD) on causespecific mortality in patients with ST elevation myocardial infarction (STEMI) treated with reperfusion therapy. Methods and results: Patients with STEMI (n = 395) treated with primary angioplasty or thrombolysis in the setting of a randomised clinical trial were enrolled in the study. Follow up was 8 (2) years. For patients who died all available records were reviewed to assess the specific cause of death. MVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 23 publications
2
36
0
2
Order By: Relevance
“…13) Although there are several studies regarding AMI with multivessel disease, 2,3,14) there have only been a few studies focusing on AMI with TVD. The mortality rate was greater in the present study (10.9%) as compared to earlier studies regarding AMI with multivessel disease 2,3) because our study did not exclude the highest mortality group such as CPA on arrival.…”
Section: Discussionmentioning
confidence: 99%
“…13) Although there are several studies regarding AMI with multivessel disease, 2,3,14) there have only been a few studies focusing on AMI with TVD. The mortality rate was greater in the present study (10.9%) as compared to earlier studies regarding AMI with multivessel disease 2,3) because our study did not exclude the highest mortality group such as CPA on arrival.…”
Section: Discussionmentioning
confidence: 99%
“…92,93 The current ACCF/AHA guidelines recommend against revascularization of the noninfarct-related arteries at the time of the index primary PCI procedure except in patients with hemodynamic instability. 18 A recent systematic review and metaanalysis showed that worse clinical outcomes associated with performing PCI of noninfarct-related stenosis during the index primary PCI procedure have been observed in nonrandomized cohort studies but not in the small number of randomized controlled trials.…”
Section: Revascularization Of Noninfarct Stenosis During Primary Pcimentioning
confidence: 99%
“…Successful and timely primary PCI leads to salvage of myocardium at risk and reduces mortality (1). Angiography before primary PCI has shown that multivessel coronary artery disease (MVD) is present in 40% to 65% of patients with STEMI and is associated with higher morbidity and mortality after reperfusion therapy (2)(3)(4)(5). A concurrent chronic total occlusion (CTO) in a non-IRA is present in 12% to 13% of patients with STEMI (2,4).…”
mentioning
confidence: 99%